1999
DOI: 10.1177/004051759906901206
|View full text |Cite
|
Sign up to set email alerts
|

Objective Evaluation of Seam Pucker Using Artificial Intelligence Part III: Using the Objective Evaluation Method to Analyze the Effects of Sewing Parameters on Seam Pucker

Abstract: The new objective evaluation method of seam pucker reported in Parts I and II of this study is used to analyze the effects of sewing parameters on seam pucker with five shape parameters in this part of the series. The parameters of sewing thread tension and stitch length are varied. To measure needle and bobbin thread tensions, frames are modified with dial tension gauges, linear guides, and weights. Four lightweight synthetic fabrics are used for seam pucker experiments. The needle and a bobbin. threads are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Similar variation tendencies have also been demonstrated by analysis the length of the puckered section l v . Research works carried out by other authors showed in the same manner that stitch length has influence on quantity of puckers but has no influence on other characteristics [22]. According to recommendations of the authors, puckering shall be decreased by changing the tensioning value of a sewing thread rather than the stitch length.…”
Section: Resultsmentioning
confidence: 93%
“…Similar variation tendencies have also been demonstrated by analysis the length of the puckered section l v . Research works carried out by other authors showed in the same manner that stitch length has influence on quantity of puckers but has no influence on other characteristics [22]. According to recommendations of the authors, puckering shall be decreased by changing the tensioning value of a sewing thread rather than the stitch length.…”
Section: Resultsmentioning
confidence: 93%
“…Th e eff ect of sewing parameters on seam pucker was examined most frequently [13,14]. Researchers have been investigating the relationship between fabric sewability, optimization of sewing and fabric features to predict seam pucker [15,16]. People prefer cotton shirts due to their soft ness and natural feeling; however, the soft -to-touch quality brings along less resilience and durability.…”
Section: Izvlečekmentioning
confidence: 99%